Experimental study on natural circulation cooling system for core catcher with downward-facing heating channel - Seokgyu Jeong; Byeonghee Lee; Jun-young Kang; Seong Ho Hong; Chang Wan Kang; Jin Hyeok Kim (Nuclear Engineering and Technology)
Core catchers are severe accident mitigation devices designed to prevent containment failure in nuclear power plants. In Korea, certain export-oriented nuclear reactors have adopted the PECS (Passive Ex-vessel corium retaining and Cooling System) core catcher design. This study investigates the cooling performance of this conceptually designed core catcher, PECS, using a scaled experimental facility, VPEX (Variable PECS EXperimental facility). The results showed that the cooling performance was satisfactory at an average heat flux value of 232 kW/m2, which is 1.75 times higher than predicted heat flux value. Furthermore, hydraulic and heat transfer characteristics for large-scale downward-facing heating channels were analyzed. It was observed that the large-scale facility exhibited relatively low heat transfer coefficient values compared to common laboratory scale facilities. Lower inlet pressures and less subcooling enhanced natural circulation mass flow rates and void fractions. Variations in inlet pressure, subcooling, or heat flux had minimal impacts on surface heat transfer characteristics such as boiling curves or heat transfer coefficients. Based on these experimental findings, the NCir (Natural Circulation calculator) analysis code was developed. The Wallis model provided the most accurate predictions for void fraction and natural circulation mass flow rate calculations. The experimental results and prediction code have potential applications in future PECS analyses. Additionally, they serve as fundamental data for large-scale facilities with downward-facing heating structures similar to VPEX.